Intertemporal Changes of The Influence of Environmental Degradation on Migration: The Case Between Malaysia and Asia-Pacific Countries - Wilson Ow Chee Seong; Baharom Abdul Hamid; Muzafar Shah Habibullah (Kajian Malaysia, 2015)
The purpose of this study is to determine the intertemporal changes that occurred in 1990 and 2000 in the link between migration and environmental degradation in the Asia Pacific region. The study used carbon dioxide emission index, gross domestic per capita income, consumer price index and distance among the countries to conduct a cross-sectional analysis to investigate this relationship. Two different points of time were regressed cross-sectionally and White standard was employed to remove traces of heterogeneity. Results clearly indicated that intertemporal effects between 1990 and 2000 were negligible. Overall, the study found that in the case of Malaysia and Asia Pacific countries, there had been no significant relationship between environmental degradation on emigration. However, other factors such as difference in the price level and inter-country distance influenced emigration significantly. Environment degradation, difference in price level and inter-country distance were found to be insignificant in influencing immigration.